A Note on the Amortization of Fixed Assets. - Wells, M. C. (The Accounting Review, 1968)
Abstract Concepts of depreciation which are relevant to accounting range from the methodical distribution of original cost, to attempts to measure and report changes in the service potential of the asset, using a discounting procedure. Allocation methods accept the distribution concept of depreciation whether this is related to original cost or some other figure, and attempt to answer the more pragmatic problem of how much is to be allocated to different periods. There is a prevailing confusion related to the definition of depreciation. One of the main causes of this confusion appears to lie in the usage of the word depredation which by its nature and common usage carries with it implications of physical deterioration, impaired efficiency, obsolescence and so on. It is suggested that, in view of the obvious confusion caused by this conflict in terminology, accountants would be well advised to restrict themselves to using the term amortization. The point that should be considered is whether the concept of amortization which is proposed is compatible with the accounting model with which it is to be associated.